Mid-Atlantic Freshwater Wetlands: Advances in Wetlands Science, Management, Policy, and Practice - Brooks, Robert P.; Wardrop, Denice Heller; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Mid-Atlantic Freshwater Wetlands: Advances in Wetlands Science, Management, Policy, and Practice summarizes over two decades of work by Riparia, a Center at The Pennsylvania State University. This comprehensive book delves into the ecology and conservation of these critically important and valued ecosystems. The 14 chapters written or edited by Riparia$1 (Bs leadership and colleagues, focus on understanding the ecology of freshwater wetlands and the stressors that affect them in a watershed context. Wetlands are viewed not as isolated patches, but as part of an integrated aquatic and terrestrial system. Early chapters address concepts of reference and hydrogeomorphic classification. The current state of our knowledge about hydrology, hydric soils, plants, and wildlife is covered in the middle chapters. Later chapters include policy issues and practice, with emphases on monitoring and assessment, restoration and mitigation, and conservation and regulatory programs. There are extensive reviews and listings of recent literature, and linkages to Riparia$1 (Bs website where supplemental information can be found.s
Foreword -- Aquatic Landscapes: The Importance of Integrating Waters -- Hydrogeomorphic (HGM) Classification, Inventory, and Reference Wetlands -- Linking Landscape to Wetland Condition: A Case Study of Eight Headwater Complexes in Pennsylvania -- Hydrology of Mid-Atlantic Freshwater Wetlands -- Hydric Soils of Mid-Atlantic Freshwater Wetlands -- Hydrophytes of the Mid-Atlantic Region: Ecology, Communities, Assessment, and Diversity -- Wetland-Riparian Wildlife of the Mid-Atlantic Region: An Overview -- Wetland-Riparian Birds of the Mid-Atlantic Region -- Assessing Wetland-Riparian Amphibian and Reptile Communities of the Mid-Atlantic Region -- Freshwater Macroinvertebrates of the Mid-Atlantic Region -- Monitoring and Assessment of Wetlands: Concepts, Case Studies, and Lessons Learned -- Wetlands Restoration and Mitigation -- Policy and Regulatory Programs Affecting Wetlands and Waters of the Mid-Atlantic Region -- Conservation and Management of Wetlands and Aquatic Landscapes: The Vital Role of Connectivity -- Index.
Keywords: Environmental sciences; Aquatic biology; Nature Conservation; Marine Sciences; Environment; Marine & Freshwater Sciences; Nature Conservation; Freshwater & Marine Ecology